SIMILARITIES OF SOME BASIC NOTIONS IN ENGLISH AND TOBA BATAK LANGUAGE - Marisi Debora (BAHAS, 2009)
In linguistics, the scientific study of meaning is called semantics. It covers the topic of some basic notions: sentences, utterances, propositions, reference and sense. The basic notions are described in such a way by finding the similarities of them in two languages (English and Toba Batak Language). It is aimed to enhance the comprehension of some basic notions in semantics.   Key words:  similarities, basic notions, semantics.